Combination of laparoscopic side-to-end colorectal anastomosis and vaginal nose (natural orifice specimen extraction) surgery for colorectal endometriosis: Technique and outcomes. Issue 3 (September 2022) - Kale, Ahmet; Kuru, Betul; Baydili, Kursat Nuri; Cokay, Deniz; Basol, Gulfem; Cansu Gundogdu, Elif; Mat, Emre; Ertugrul, Ismail; Altuntas, Yunus Emre; Usta, Taner; Aboalhasan, Yasmin; Oral, Engin
Objective: To investigate the effectiveness of combining side-to-end anastomosis and vaginal NOSE (Natural orifice specimen extraction) surgery in colorectal endometriosis. Material and methods: We included 11 patients treated with laparoscopic side-to-end colorectal anastomosis and vaginal NOSE surgery between January 2019 and May 2021. We questioned the visual analog score (VAS) for pain symptoms, the short form-36 (SF-36) for health survey questionnaire, The Female Sexual Function Index (FSFI), EHP-5 for endometriosis health profile, The Hospital Anxiety and Depression Scale (HADS), OAB-V8 for overactive bladder symptoms and Constipation Severity Instrument (CSI). Results: VAS, EHP-5, and SF-36 scores were better at postoperative third and sixth months than preoperative values ( p  < 0.05). There were no statistically significant differences in terms of FSFI, OAB-V8, HADS, and the CSI. Conclusions: Laparoscopic side-to-end anastomosis with vaginal NOSE surgery is feasible, scarless, and could be offered to patients with deep symptomatic bowel endometriosis.